Effect of adding aminophylline infusion to nebulised salbutamol in severe acute asthma. Issue 3 (March 1994) - Zainudin, B M; Ismail, O; Yusoff, K
Abstract : BACKGROUND--The benefit of adding theophylline to beta 2 agonists in acute asthmatic attacks has been debated frequently. METHODS--In an open randomised study 25 patients with severe acute asthma who presented to the emergency department were treated with either a combined nebulised salbutamol (5 mg/dose) and aminophylline infusion (0.6-0.9 mg/kg/hour), or nebulised salbutamol alone. RESULTS--The responses to treatment as measured by peak expiratory flow (PEF) and the time taken to achieve maximum PEF were similar in both groups. Side effects were observed more commonly in patients receiving the combined treatment. CONCLUSIONS--Nebulised salbutamol is equally efficacious in acute asthma when given alone or in combination with aminophylline.